On the Homeric Hymns and Prayer - Abritta, Alejandro (Classica - Revista Brasileira de Estudos Clássicos, 2015)
The purpose of this paper is to study the possible relation between prayer and the long Homeric Hymns. The analysis centers on the beginnings and endings of these compositions, in which two of the traditional parts of prayer are found. The paper opens with a brief account of the problem, its goals and methodology. Then, after a general introduction on hymnody and prayer, the author analyzes two hymns, the Homeric Hymn to Delian Apollo and the Homeric Hymn to Hermes, in order to show that in these compositions there is a development of the beginning, the invocatio, and of the ending, the request. The goal is to prove that there is an attentive expansion of the basic elements of these sections, and therefore that these poems were actual cultic compositions to achieve the good will (χάρις) of the gods.